2016
DOI: 10.1039/c6ra19921f
|View full text |Cite
|
Sign up to set email alerts
|

Enzymeless biosensor based on β-NiS@rGO/Au nanocomposites for simultaneous detection of ascorbic acid, epinephrine and uric acid

Abstract: In this study, marigold flower-like self-assembled β-NiS (nickel sulfide) nanosheets were grown on rGO (reduced graphene oxide) by a single-step hydrothermal process and then gold nanospheres (AuNS) were electrochemically deposited on the β-NiS@rGO nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…However, in vivo situations are far complex than buffer solutions, with the presence of over thousand-fold higher concentrations of interferent molecules. AA and UA, which share similar electrochemical profiles with adrenaline, represent two major interferents with 60 μM AA and 250 μM UA in human blood . We mimicked the in vivo situation and evaluated the sensor performance with the coexistence of these two major interferents at high concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo situations are far complex than buffer solutions, with the presence of over thousand-fold higher concentrations of interferent molecules. AA and UA, which share similar electrochemical profiles with adrenaline, represent two major interferents with 60 μM AA and 250 μM UA in human blood . We mimicked the in vivo situation and evaluated the sensor performance with the coexistence of these two major interferents at high concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…AA and UA, which share similar electrochemical profiles with adrenaline, represent two major interferents with 60 μM AA and 250 μM UA in human blood. 31 We mimicked the in vivo situation and evaluated the sensor performance with the coexistence of these two major interferents at high concentrations. Figure 3b-ii shows the increased CV responses due the high background electrochemical reaction from AA and UA.…”
Section: Integrated Electrochemical Sensing Of the Fibermentioning
confidence: 99%
“…As even 100 repeated continuous electrochemical cycles in 0.1 mM RF solution ( Figure 9 A) do not modify the film stability and do not cause leaching of the adsorbed RF, it can be concluded that RF strongly oxidizes the modified electrode surface. 37 , 38 Moreover, the contact of the modified electrode with air does not cause loss of electroactivity. The strong binding is believed to be due to the P–P interaction of the aromatic ring, as well as the NH group of RF with Gd 2 O 3 nanosheets deposited on the modified electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the gold nano‐spheres were deposited electrochemically. The fabricated electrode had a linear response in the range 900 nM–100 μM and 100 nM–1.0 mM with limits of detection of 331 nM and 4.5 nM for AA and UA, respectively …”
Section: Sensors and Biosensorsmentioning
confidence: 99%